PENGARUH INSTRUMEN KEUANGAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI INDONESIA - FARMA ANDIANSYAH; SYAFIQ MAHMADAH HANAFI; SLAMET HARYONO; TAOSIGE WAU (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2022)
The growth of Islamic finance in Indonesia has experienced very significant growth. The Indonesian government hopes that the financial sector will become an important instrument in promoting economic growth in Indonesia, but it seems that the percentage of economic growth in Indonesia has declined over the past decade. This study aims to analyze the impact of Islamic financial instruments on economic growth in Indonesia. This study uses a quantitative method with an Autoregressive Distributed Lag (ARDL) model analysis tool. The results of this study show that all Islamic financial instrument variables have a negative effect on economic growth in the short term. Meanwhile, in the long term, all independent variables have a positive effect on economic growth except for Sharia Mutual Funds which show a negative effect and Sharia Bank Financing and Sharia Stocks have no effect on economic growth in Indonesia. Thus, it can be concluded that Islamic financial instruments in the long term have a positive influence on encouraging economic growth in Indonesia.